Pertanggungjawaban Hukum Perbuatan Kampanye Hitam (Black Campaign) dalam Pemilu Melalui Media Sosial - Abd Karim; Moh Zeinudin; Slamet Suhartono (JURNAL HUKUM PELITA, 2025)
This article examines black campaigning on social media during the general election and its legal liability. Using legislative and conceptual approaches, normative legal research is done. Primary, secondary, and tertiary legal materials are used. Legal materials are analysed descriptive-qualitatively. Black political campaigns routinely abuse social media to attain their goals. The Law on General Elections and the General Election Commission Regulation on General Election Campaigns in Indonesia govern social media use in campaigns to combat this. The Law on General Elections and the Law on Information and Electronic Transactions penalise social media black campaigning with fines and jail time. Such actions are election crimes and cybercrimes since they involve technology